Evaluation of rural municipalities’ (Dehyari) performance in realization of social sustainability of the villages Case study of central part of Nimroz city of Sistan - Palash, Abbas; Ja’fari, Hamid; Darban, Hadi Ghanbarzadeh (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2022)
In recent decades, social sustainability has become the center of many researchers and planners’ attention. In this regard, one of the main approaches to achieve social sustainability is paying attention to the role of rural municipalities. Regarding the importance of this subject, the current study aimed to evaluate the rural municipalities’ performance in the achievement of social sustainability in the Central District of Nimrouz County. The current study is of applied type in terms of objective and it is of descriptive-analytical type in terms of methodology. The data collection instruments were questionnaires and interviews, and the statistical population included the rural households in the central district of Nimrouz County. The data were analyzed by the One-Sample t-test and the variance analysis and multivariable regression were also used to evaluate the rural governor’s (Dehtar) performance. The results indicated that rural governors’ performance in the social sustainability of the villages under study has managed to grab local villagers’ satisfaction and it was at an appropriate level.